2023
DOI: 10.2215/cjn.0000000000000105
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Participants with CKD and Other Kidney-Related Considerations during Clinical Drug Development

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 19 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…This is likely because the original trials of chemotherapeutics determine dose thresholds were based on CG estimations of CrCl. Oncology research continues to use CG in trials today 5 . For example, a 2017 research letter described a random sample of active, Phase I‐III, cisplatin‐based clinical trials and showed that only 2% of studies used eGFR to define kidney function thresholds 23 .…”
Section: Practical Considerations For Estimating Gfr In Oncologymentioning
confidence: 99%
See 4 more Smart Citations
“…This is likely because the original trials of chemotherapeutics determine dose thresholds were based on CG estimations of CrCl. Oncology research continues to use CG in trials today 5 . For example, a 2017 research letter described a random sample of active, Phase I‐III, cisplatin‐based clinical trials and showed that only 2% of studies used eGFR to define kidney function thresholds 23 .…”
Section: Practical Considerations For Estimating Gfr In Oncologymentioning
confidence: 99%
“…While a large proportion of the studies (61%) used CG‐based estimation of CrCl or serum creatinine alone, 33% did not articulate any kidney function threshold for trial inclusion 23 . These data expose the imprecision and inconsistency of methods used to estimate kidney function in cancer clinical trials 5,23 …”
Section: Practical Considerations For Estimating Gfr In Oncologymentioning
confidence: 99%
See 3 more Smart Citations